2019
DOI: 10.1007/s11370-019-00283-w
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of haptic guidance virtual fixtures and 3D visualization methods in telemanipulation—a user study

Abstract: This work presents a user-study evaluation of various visual and haptic feedback modes on a real telemanipulation platform. Of particular interest is the potential for haptic guidance virtual fixtures and 3D-mapping techniques to enhance efficiency and awareness in a simple teleoperated valve turn task. An RGB-Depth camera is used to gather real-time color and geometric data of the remote scene, and the operator is presented with either a monocular color video stream, a 3D-mapping voxel representation of the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…Alternatively wearable Virtual Reality devices could be used. Finally, if haptic feedback is applied ( Delft Haptics Lab, 1994 ; Barros et al, 2015 ; Hoshino et al, 2018 ; Huang et al, 2019 ; Protocom, 2022 ), the user may be able to “feel their way” through environments with limited vision or feel objects buried in sand.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively wearable Virtual Reality devices could be used. Finally, if haptic feedback is applied ( Delft Haptics Lab, 1994 ; Barros et al, 2015 ; Hoshino et al, 2018 ; Huang et al, 2019 ; Protocom, 2022 ), the user may be able to “feel their way” through environments with limited vision or feel objects buried in sand.…”
Section: Discussionmentioning
confidence: 99%
“…Haptics are promising because users can feel the terrain through the force feedback and adjust the gait, which aids balance when walking in 3D terrain. Current haptic devices being applied in teleoperation of legged robots include Phantom Omni ( DelftHapticsLab, 1994 ; Barros et al, 2015 ; Huang et al, 2019 ) and Touch 3D stylus ( Hoshino et al, 2018 ; Protocom, 2022 ). With one device paired with one tripod gait group, the operators are able to control the movement of robot legs ( Huang et al, 2021 ), as shown in Figure 2C .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies confirm that a virtual environment where one can change its sight-of-view and provide haptic guidance (e.g. virtual fixtures) improves the system capabilities [11]- [13].…”
Section: Introductionmentioning
confidence: 89%
“…For example, an unbounded linear effect having a positive slope results in guidance VFs (Van Oosterhout et al, 2019). A bounded nonlinear effect results in a guidance VF that is helpful when visual and haptic feedback are used (Huang et al, 2019). A negative half-plane effect with a negative slope results in forbidden-region VFs (Li et al, 2007).…”
Section: Description Of Component "Geometry"mentioning
confidence: 99%